Materials - Gifford, Clive (Discover science (Kingfisher (Firm)), 2012)
Describes the properties of different types of natural and manufactured matter, including elastic, marble, wood, silk, and gold. Materials answer fundamental questions about the matter and materials that make up the physical world around us. What are rocks made of? Where do plastics come from, and what are they used for? Why can I see through glass? Readers are introduced to the most common natural and manufactured materials-including metals, wood, paper, cotton, and recycled products--and learn why some are hard and others are malleable and why some stretch while others snap.